Shifting “Reproductive Work” To The Public: “Nakorn Chum Retro-Market” And “Traditional Foods” Selling As Space Of Aging Women In Kamphaeng Phet Province, Thailand - Chotiwan, Phurinat (2016)
“Nakorn Chum Retro Market” is a type of walking street market and held at the beginning of every month. To construct nostalgic sentiment, the retro market is held in the area of “Nakorn Chum” ancient city where was ever the center of commerce in the past century. The nostalgic sentiment of the retro market are composed of cultural components such as dressing in the traditional Thai costumes, Thai dancing shows and local handicrafts etc. but the highlight of market is “Traditional Foods”. Cooking “Traditional foods” is required skill and knowledge from the aging persons who can claim the “original recipe” especially women. So, can be seen that the most of food sellers in the retro market are aging women who use their cooking skill which always seen as “Reproductive Work” in Domestic Sphere to do in the Public and in the space of retro market, economic and cultural value were added into reproductive work, such cooking “Traditional Food”. In this paper, “Nakorn Chum Retro Market” is considered as social space of aging women. The paper aims to explore the roles of aging women in“Nakorn Chum Retro Market” and argues that in the structure of power, women are not merely passive victims but they are active agents. They try to negotiate their position as much as they can under the limitations. They use feminine attributes and skills from reproductive work in domestic sphere which they are familiar to be advantage for themselves in public space such the retro market that why author titled “Shifting Reproductive Work to the Public:“Nakorn Chum Retro Market” as Space of Aging Women in Kamphaeng Phet Province, Thailand”.